Achieving Dual‐Emissive and Time‐Dependent Evolutive Organic Afterglow by Bridging Molecules with Weak Intermolecular Hydrogen Bonding. Issue 7 (22nd January 2019) - Chen, Junru; Yu, Tao; Ubba, Eethamukkala; Xie, Zongliang; Yang, Zhiyong; Zhang, Yi; Liu, Siwei; Xu, Jiarui; Aldred, Matthew P.; Chi, Zhenguo
Abstract: It is discovered that "bridging" traditional persistent room‐temperature phosphorescence (pRTP) dibenzofuran moieties by intermolecular hydrogen bonding can induce interesting photophysical properties. The light‐emitting material 4‐(4‐((4‐methoxyphenyl)sulfonyl)phenyl)dibenzo[b, d]furan (SOBF‐OMe) is synthesized and excitingly shows novel dual‐emissive afterglow material properties in which orange pRTP (at ≈580 nm, 627 ms) from the dibenzofuran moiety and another blue ultralong intermolecular charge transfer emission (≈476 nm, 204 ms, with TADF characteristics) can be detected. Due to the different decay lifetimes, the ratio of the two afterglow emission bands continuously changes. Accordingly, the emission colors are unusually tuned gradually from cold‐white to orange during the afterglow decay process. The blue afterglow emission, which relates to intermolecular interactions, is sensitive to mechanical stimuli and the afterglow emission properties of SOBF‐OMe (single‐emissive or dual‐emissive) can easily be manipulated by grinding/fuming. This single‐component material is a rare example of a light‐emitting compound showing dual‐emissive and real‐time changing afterglow properties in which a rational bridging strategy via weak intermolecular hydrogen bonding is utilized. Abstract : Achieving Dual‐Emissive Organic Afterglow in Single‐Component : In this study, a dual‐emissive organic afterglow material with reliable strategy is achieved. The afterglow colors are unusually and naked‐eye visible tuned gradually from cold‐white to orange in real‐time during the afterglow decay process due to the different decay lifetimes of the two afterglow emission bands.